Mobile Phone Banking Usage Behaviour: An Australian Perspective - Majharul Talukder; Ali Quazi; Milind Sathye (Australasian Accounting, Business and Finance Journal, 2014)
While the use of mobile phones in financial transactions is witnessing phenomenal growth at the international level, its growth has been relatively slow in Australia. Drawing on the theory of reasoned action and technology adoption framework, this paper reports the results concerning a survey of mobile phone users for banking transactions in Australia. The paper specifically identified the factors affecting usage behaviour when mobile phone banking services were engaged. The findings broaden and deepen our understanding of the usage of mobile-based banking in the information age. This paper contributes to the knowledge of this subject by including identification and testing of constructs of predictors regarding mobile phone banking, which are additional to those employed in the extant theories indicated above. The findings of this paper have important policy implications for banks in terms of understanding the underlying factors that drive customers’ mobile banking for financial transactions. Accordingly, design strategies have been developed to promote mobile phone banking – a cost effective channel for delivering financial services.
Keywords: Mobile phone banking; usefulness; credibility; system quality; social influence; usage level